2017
DOI: 10.1016/j.jinf.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin non-susceptible Enterococcus faecium in leukemia patients: Role of prior daptomycin exposure

Abstract: Summary Objectives We sought to determine the association between previous daptomycin exposure and daptomycin non-susceptible Enterococcus faecium (DNSEf) bloodstream infections (BSI) in adult leukemia patients. Methods We retrospectively identified adult (≥ 18 years old) leukemia patients with Enterococcus spp. bacteremia at The University of Texas MD Anderson Cancer Center (MDACC) from 6/1/2013 to 7/22/2015. Antimicrobial susceptibility and previous antibiotic exposure within the 90 days prior to bacterem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…VRE is one of the most difficult-to-treat pathogens, and daptomycin is often considered the drug of choice for the treatment of serious VRE infections. However, daptomycin is also for several other indications, and prior exposure to daptomycin for any reason can lead to subsequent daptomycin-resistant VRE (14). This case highlights this key point, wherein brief exposure to daptomycin for a complicated MRSA bacteremia likely contributed to the development of a hardware-associated spinal infection caused by daptomycin-resistant VRE.…”
Section: Commentarymentioning
confidence: 88%
“…VRE is one of the most difficult-to-treat pathogens, and daptomycin is often considered the drug of choice for the treatment of serious VRE infections. However, daptomycin is also for several other indications, and prior exposure to daptomycin for any reason can lead to subsequent daptomycin-resistant VRE (14). This case highlights this key point, wherein brief exposure to daptomycin for a complicated MRSA bacteremia likely contributed to the development of a hardware-associated spinal infection caused by daptomycin-resistant VRE.…”
Section: Commentarymentioning
confidence: 88%
“…Daptomycin resistance has been shown to arise within patients during treatment [19]. Additionally, a number of studies have reported prior daptomycin treatment as a key risk factor for infection with daptomycin resistant VRE [20][21][22], which is consistent with offtarget selection. Finally, transmission of VR E. faecium is common in hospital settings, meaning resistance that arises in one patient may pose a threat to others.…”
Section: Introductionmentioning
confidence: 88%
“…Nowadays, no data are present in the literature on efficacy of fidaxomicin in patients with severe CDI, so in patients with severe disease metronidazole should be added. Despite the fact that resistance to DAP among staphylococci and enterococci is uncommon, some studies highlight the issue of increasing resistance [17][18][19]. Otherwise, we recommend high-dose DAP in association with CPT, independently to DAP susceptibility test.…”
Section: Expert Opinionmentioning
confidence: 96%